Crip times : disability, globalization, and resistance - McRuer, Robert, 1966- (Crip (Series), 2018)
Contends that disability is a central but misunderstood element of global austerity politics. Broadly attentive to the political and economic shifts of the last several decades, Robert McRuer asks how disability activists, artists and social movements generate change and resist the dominant forms of globalization in an age of austerity, or "crip times." Throughout Crip Times, McRuer considers how transnational queer disability theory and culture--activism, blogs, art, photography, literature, and performance--provide important and generative sites for both contesting austerity politics and imagining alternatives. The book engages various cultural flashpoints, including the spectacle surrounding the London 2012 Olympic and Paralympic Games; the murder trial of South African Paralympian Oscar Pistorius; the photography of Brazilian artist Livia Radwanski which documents the gentrification of Colonia Roma in Mexico City; the defiance of Chilean students demanding a free and accessible education for all; the sculpture and performance of UK artist Liz Crow; and the problematic rhetoric of "aspiration" dependent upon both able-bodied and disabled figurations that emerged in Thatcher's England. Crip Times asserts that disabled people themselves are demanding that disability be central to our understanding of political economy and uneven development and suggests that, in some locations, their demand for disability justice is starting to register. Ultimately, McRuer argues that a politics of austerity will always generate the compulsion to fortify borders and to separate a narrowly defined "us" in need of protection from "them"